2010
DOI: 10.1177/0009922810378735
|View full text |Cite
|
Sign up to set email alerts
|

Most Common Sports-Related Injuries in a Pediatric Emergency Department

Abstract: Football and basketball related injuries are common complaints in a pediatric Emergency Department. Frequently seen injuries include CHI, fractures and lacerations. In our institution, fractures were more prevalent among football players and CHI was more prevalent among organized sports participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 7 publications
2
14
1
1
Order By: Relevance
“…Several studies that have examined the nature of sport-related injuries among youth reported that fractures were most frequently evaluated in the emergency departments [1,5,10,17]. A study performed by Taylor and Attia in 2000 showed that fractures accounted for 29.4% of all sports-related diagnoses [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies that have examined the nature of sport-related injuries among youth reported that fractures were most frequently evaluated in the emergency departments [1,5,10,17]. A study performed by Taylor and Attia in 2000 showed that fractures accounted for 29.4% of all sports-related diagnoses [15].…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains unclear whether males or females are more likely to sustain SRIs and how these injuries vary by sport. In the United States, football, basketball and baseball cause the greatest number of sports-related injuries in children but this varies by age, sex, and sport [5,7-10]. …”
Section: Introductionmentioning
confidence: 99%
“…Participation in athletics can be of enormous physiologic and psychological benefit, potentially of lifelong effect. However, sports and recreational activities include a certain amount of risk of injury; over 4 million sports or recreational injuries are sustained by school-age children in the USA every year [2]. Pediatric and adolescent athletes differ from adults in several important ways that likely contribute to injury susceptibility: decreased balance and coordination as well as inflexibility while bone growth outpaces that of muscle and tendon, open physes, and growing cartilage [3].…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that over four million sports or recreational injuries occur in children and young adults each year in the United States [ 1 ]. These include elbow, shoulder, and hip disorders, back pain, and concussions, among others.…”
mentioning
confidence: 99%